Investigation of particle effects on bubble coalescence in slurry with a chimera MP-PIC and VOF coupled method. (16th January 2023) - Liao, Yixiang; Wang, Qingdong; Caliskan, Utkan; Miskovic, Sanja
Highlights: Film drainage and bubble coalescence is investigated with high-resolution numerical methods. Effect of particles and their properties on thin liquid film drainage and rupture is studied in detail. The influence of particle concentration on the coalescence time in co-axial cases is multmodal. Particles may block coalescence, change drainage axisymmetry and affect film instability. Wake entrainment is a key factor influencing coalescence in bubble columns. Abstract: Bubble coalescence and breakup is still a complex challenging topic. How far it is understood affects directly the analysis and design optimization of multiphase reactors. Despite years of active research, bubble coalescence in three-phase systems is far from being understood. Contradictory results on the effect of particles are often reported. Although it still lacks a unique explanation, a general conjecture is that the presence of solid particles affects the film drainage process, and hence the bubble coalescence time and behaviour. This paper presents insights into bubble-pair coalescence in slurry by coupling the multiphase particle in cell (MP-PIC) method with the volume of fluid (VOF) method. The mesh resolution for VOF fields is down to micrometers, which allows for analysis of the film drainage and rupture mechanism in detail. The accuracy of MP-PIC fields during the refinement of CFD grids is guaranteed by a chimera approach (Caliskan and Miskovic, Chemical Engineering Journal Advances 5 (2021) 100054), which allows two overlapping meshes in the Lagrangian–Eulerian framework, namely, a fine mesh for the CFD fields and a coarser mesh for the MP-PIC ones.